PLICATURA GÁSTRICA - Fallas González, Jorge (2011)
In bariatric surgery several different techniqueshave been developed, with different mechanismsof action and indications; recently gastricplication has been implemented as an alternative for the treatment of morbid obesity. It has shownresults of excess weight loss compared to othertechniques such as gastric sleeve. It also offersdistinct advantages over other proceduresbecause of the non-resective nature of plication. Being a new technique, we describe it andpresent the most important results obtained sofar.